Race, housing & community : perspectives on policy & practice - Beider, Harris (Chichester, West Sussex [England] : John Wiley & Sons, 2012)
"This book provides an important new contribution to debates around housing policy and its impact on community cohesion. There has never been a more prescient time to discuss these concepts: the book provides an interpretation of housing, race and community cohesion in a highly politicized and fluid policy context. It is designed to initiate discussion and debate but this should not be esoteric and limited to a group of academics. Rather the objective is to bridge academic and policy audiences in the hope that this fusion provides a basis for a new agenda to discuss these topics. Race and community have been key features of social housing policy over the last 20 years with many high-profile interventions, from the proactive approach by the Housing Corporation to support black and minority ethnic housing associations, to the influential Cantle Report documenting segregation in towns and cities following riots, and the National Housing Federation led Race & Housing Inquiry leading to sector wide recommendations to achieve equality. However, volume of policy interventions and reports has not been matched by academic outputs that co-ordinate, integrate and critically analyse 'race', housing and community. Housing, Race & Community Cohesion is the first systematic overview of 'race', housing and community during this tumultuous period. The material presented is robust and research based but also directly engages with issues around policy and delivery. It is designed to reflect the interests both of the academic research community and policy makers on both sides of the Atlantic"-
Front Matter -- Race, Housing and Community -- Housing Policy and Practice -- Developing Cohesive Neighbourhoods in UK Cities: White Perspectives -- The Emergence of the Black Led Housing Sector -- Housing, Communities and 'Recycled Racism' -- New Frameworks for Race, Housing and Community -- Appendix A--Public Service Futures: The Future of Identify and Belonging (OPM) -- Appendix B--LGA Guidance on Community Cohesion -- Appendix C--Three Definitions of Community Cohesion -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Housing policy -- Great Britain; Community development -- Great Britain; Race discrimination -- Great Britain; Racism -- Great Britain; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; Community development; Housing policy; Race discrimination; Racism; Great Britain; Electronic books; Electronic books